Exploring the influence of audiences subjective well-being in sport event: the moderating role of leisure engagement - Wu,Jiayu (2020)
Drawing on leisure coping theory, this study examines how negative impacts of sport events influence audiences subjective well-being, which further affects the support of the event. Leisure engagement is further employed to test its moderating effect of this relationship. By distributing questionnaires on-site during the on-going four days of the Macau Grand Prix 2018, 620 valid audiences were surveyed. The findings suggest that (a) audiences perceived negative impact of the Macau Grand Prix negatively influence their subjective well-being, (b) when the leisure engagement was low, the negative relationship between negative impact of the Macau Grand Prix and audiences subjective well-being was alleviated, and (c) the indirect effects of audiences perceived negative impact on support for sport events via subjective well-being was buffered by leisure engagement, such that the indirect effects were only found in dyads with lower leisure engagement, but not in dyads with higher leisure engagement. Theoretical contribution and practical implications for Macau government and organization of the Macau Grand Prix were also discussed.